1982
DOI: 10.1080/03079458208436091
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of PMV‐3/parakeet/netherlands/449/75 for chickens

Abstract: SUMMARYInfection of 1-day-old chicks with PMV-3/parakeet/Netherlands/449/75 (449) by intramuscular, intranasal or contact routes resulted in severe impairment of growth in all groups compared to uninfected control birds. In the group infected intramuscularly with 449 virus 16/22 birds died within 14 days of infection.No clinical signs were seen in 6-week-old chickens infected with 449 by intramuscular, intranasal or contact routes.One-day-old chicks infected with a large dose of NDV-B 1 and one-dayold chicks p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…In contrast to the well-studied APMV1 or NDV, very little is known about the biological characteristics, pathogenicity, and diversity (both genetic and antigenic) of other APMV serotypes 2-10. APMV types 2, 3, 6 and 7 have been associated with disease in domestic poultry [7-13]. APMV6 viruses have been associated with mild respiratory disease and decreased egg production in turkeys [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the well-studied APMV1 or NDV, very little is known about the biological characteristics, pathogenicity, and diversity (both genetic and antigenic) of other APMV serotypes 2-10. APMV types 2, 3, 6 and 7 have been associated with disease in domestic poultry [7-13]. APMV6 viruses have been associated with mild respiratory disease and decreased egg production in turkeys [14].…”
Section: Introductionmentioning
confidence: 99%
“…The poor recovery of virus from respiratory tract and brain may have resulted from the use of cell-free inocula because the regular recovery of NDV from different parts of the brain required co-cultivation (Wilczynski et al, 1977). Another PMV-3, 449 of psittacine origin, has been considered as a potential pathogen of chickens because it can reproduce experimental disease and stunting (Alexander and Collins, 1982) with lethality of one-day-old birds resulting from intramuscular but not intranasal or contact virus. However, MPHV was less pathogenic than 449 to chickens because no stunting or seroconversion followed contact exposure to virus and its mean ICPI of 0.41 was less than the value of 1.37 for 449 reported by Alexander and Chettle (1978) or 0.62 for 449 obtained here.…”
Section: Protection By Mabsmentioning
confidence: 99%
“…In another study, it was shown that the extent of disease and death in the birds after infection with APMV-3 strain Netherlands depends on dose as well as route of infection (Alexander and Collins, 1982b). The clinical signs of illness were more evident in 1-day-old birds compared to 2-weeks-old birds.…”
Section: Outcome Of the Studymentioning
confidence: 98%
“…These results confirmed previous findings that chickens and turkeys are susceptible to APMV-3 infection. Furthermore, younger birds are more susceptible than older birds (Alexander and Collins, 1982b;Russell et al, 1989). …”
Section: Outcome Of the Studymentioning
confidence: 99%
See 1 more Smart Citation